Mechanical Phenomenon of Moving Charged Particles in Electromagnetic Field - Karki, Ravi; Adhikari, Dipak; Adhikari, Kapil; Pantha, Nurapati; Adhikari, Narayan Prasad (Journal of Engineering and Sciences, 2022)
Abstract available with the full text.